1854 Or. Terr. Stat. 257, ch. 37, An Act to Prohibit the Sale of Arms and Ammunition to Indians, §§ 1-3. - (:unkn) unknown (My University, 1853)
Prohibited any "white citizen" to sell, barter, or give any kind of firearm or ammunition to "an Indian."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES